Seven testaments of world religion and the Zoroastrian older testament - Brown, Brian A. 1942- (Lanham Boulder New York London Rowman & Littlefield, 2020)
Introduces the Avesta scriptures of Zoroastrianism, plus the creation stories from seven other religions and seven apocalypses, showing them all to be derivatively based on Vedic-Zoroastrian originals
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Zoroastrianism -- Relations; Creation -- Mythology; End of the world; Creation ; Mythology; Interfaith Relations; Zoroastrianism